A study of fibre bundles’ formation regularities during the impact interaction of spikes with raw cotton particles - Veliev, Fazil (Eastern-European Journal of Enterprise Technologies, 2020)
The article describes a study of the dynamics of interacting between loosening roller spikes and particles of raw cotton as well as the conditions for the raw cotton particles’ bundling. The process of movement of raw cotton particles was considered on the mesh surface of a fine impurity cleaner; a search was made for ways to intensify the process and to increase its stability. The conditions for imparting a rotational motion to the flyer were determined when the flyer was connected with the supplied layer of raw cotton. Turning the flyer against the axis will twist the fibre bundle that binds the particle to the rest of the cotton mass, and this is a prerequisite for the fibre to bundle. The value of the twist angle will depend on both the frictional force and the time of the force action, which together determine the energy spent on twisting. By piecewise linearization of the P(t) curve, the processes of shock loading and unloading of the flyer during interaction with the spike are described in good agreement with the experimental oscillograms of the process. The eccentric interaction of the spike with a particle of raw cotton was considered. The relationship of this interaction with the formation of soft defects in the fibre – bundles – was proven experimentally and theoretically. It is recommended to install spike rollers having a flat front face in the system of raw cotton pre-cleaning. The use of spikes of this shape of the front edge ensures a steady reduction in the number of bundles in the raw cotton fibre, which increases the quality of the fibre and reduces the amount of defects and impurities. As a result of the experimental and theoretical studies, data have been obtained to make it possible to organise the efficient operation of cleaning machines in the cotton ginning industry